Optimation and Sensory Profile of Functional Drink from Cinnamon and Cardamom - Mardiana Mardiana; Novriza Sativa; Hari Hariadi; Nanda Triandita; Nela Eska Putri (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2020)
Functional drinks can be made from local herbal ingredients that are often used for spices such as cinnamon (Cinnamomum burmanni) and cardamom (Amomum compactum). The purpose of this study is to determine the best formulation of cinnamon and cardamon as a herbal drink based on moisture content, ash content , and sensory evaluation. Raw materials were dried at 50 °C until reached a maximum moisture content 10% and were reduced in size. The formulations were made of comparison between cinnamon and cardamom which were A (100: 0)%; B (80:20)%; C (60:40)%; D (50:50)%; E (40:60)%; F (20:80)%; and G (0: 100)%. The moisture content of all formulas is between 7.12-7.33% (<10%) and the ash content of all formulas is between 4.83-5.06%. The results of sensory analysis showed that formula B had the best acceptance for color (3.03) and aroma (3.17). Thisproducthad moisture 7.23 % and ash content 4.83 %.